2019
DOI: 10.3389/fphys.2019.00024
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Suppresses Keratinocyte Migration Through the Inhibition of p38 MAPK/Autophagy Pathway

Abstract: Wound healing is delayed frequently in patients with diabetes. Proper keratinocyte migration is an essential step during re-epithelialization. Impaired keratinocyte migration is a critical underlying factor responsible for the deficiency of diabetic wound healing, which is mainly attributed to the hyperglycemic state. However, the underlying mechanisms remain largely unknown. Previously, we demonstrated a marked activation of p38/mitogen-activated protein kinase (MAPK) pathway in the regenerated migrating epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 39 publications
(44 reference statements)
4
62
0
Order By: Relevance
“…In addition, infection and other factors can also induce p38 MAPK activation. 48 In the present study, consistent results were achieved with TG induction in H9c2 cells, and high expression of p-p38 MAPK was found.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, infection and other factors can also induce p38 MAPK activation. 48 In the present study, consistent results were achieved with TG induction in H9c2 cells, and high expression of p-p38 MAPK was found.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, the crosstalk between MAPK and autophagy has been elucidated enormously in different cell types. 16,17 In addition, our previous study also suggests that the MAPK signaling pathway is activated on MNT surface in osteoblasts. 18 Taken together, we hypothesize that the MNT surface may induce autophagy response through MAPK pathway and consequently influence the macrophages M2 polarization.…”
Section: Introductionmentioning
confidence: 89%
“…Previous study has confirmed the expressions of LC3B and Beclin1 were significantly upregulated in rat bone marrow mesenchymal stem cells, which were stimulated in high glucose (HG) condition, with increased formation of autophagosomes . However, the dysfunction of autophagosomes was found in skin epithelium of diabetic mice, accompanied with the decrease of LC3II/I expression ratio . The imbalance of autophagy seems to be able to explain the abnormal expression of inflammatory cytokines in cells stimulated by HG.…”
Section: Introductionmentioning
confidence: 91%